Mental Health and Health-Related Behavioral Patterns Surrounding a Major International Sporting Event: An Observational Study - Gustavo A. Hernández-Fuentes; Mario A. Alcalá-Pérez; Uriel Díaz-Llerenas; Marcos E. Guerrero-Verduzco; Nancy A. Reyes-Méndez; Laura A. Larios-Gómez; Dalila G. Virgen-Aguilar; Jessica C. Romero-Michel; Verónica M. Guzmán-Sandoval; Fabian Rojas-Larios; Pedro J. Flores-Moreno; Osval A. Montesinos-López; et al. (Diseases, 2026)
Background/Objectives: Acute collective emotional events may coincide with variation across multiple dimensions of mental health and health-related behaviors. This study compared mental health outcomes and recent alcohol consumption between assessments conducted before and after a major international sporting event and explored factors associated with psychological and behavioral outcomes among young adults. Methods: An observational study was conducted among 146 adult students in western Mexico who participated in assessments surrounding the 2026 FIFA World Cup match between Mexico and England. Assessments were conducted approximately 10 h before kick-off and 11 h after completion of the match. Because individual responses could not be linked across assessment periods, comparisons were analyzed as repeated cross-sectional marginal comparisons rather than paired longitudinal analyses. Psychological outcomes were assessed using standardized instruments, and recent alcohol consumption was defined as alcohol use during the eight hours preceding each assessment. Results: Anxiety-related symptom scores were lower at the post-event assessment, whereas depressive-related symptoms remained relatively stable. Emotional well-being was also lower at the post-event assessment, while recent alcohol consumption during the eight hours preceding the assessment was substantially more frequent post-event than pre-event (41.1% vs. 0.7%). The small difference observed in sexual-attitude scores was considered exploratory. Post-event multivariable analyses identified several factors associated with psychological outcomes and recent alcohol consumption; these associations were interpreted as cross-sectional. Conclusions: Psychological and behavioral outcomes exhibited distinct patterns between assessment periods surrounding the sporting event. Given the observational design, inability to link individual responses, and presence of unmeasured co-occurring exposures, these differences should not be interpreted as within-participant changes or as effects attributable specifically to the match.